2009
DOI: 10.1007/s10704-009-9427-3
|View full text |Cite
|
Sign up to set email alerts
|

Weakly nonlinear fracture mechanics: experiments and theory

Abstract: Material failure occurs at the small scales in the immediate vicinity of the tip of a crack. Due to its generally microscopic size and the typically high crack propagation velocity, direct observation of the dynamic behavior in this highly deformed region has been prohibitively difficult. Here we present direct measurements of the deformation surrounding the tip of dynamic mode I cracks propagating in brittle elastomers at velocities ranging from 0.2 to 0.8C s . Both the detailed fracture dynamics and fractogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 64 publications
1
7
0
1
Order By: Relevance
“…Therefore, the moving crack is expected to deflect and propagate along a direction at an angle of 30 • to the original direction of crack propagation. This predicted angle is close to the experimental value of 25 • for PMMA [23], which has been shown to have similar dynamic crack oscillation behavior to polyacrylamide gels [5].…”
Section: ) Crack Branching At High Crack Speedsupporting
confidence: 85%
See 1 more Smart Citation
“…Therefore, the moving crack is expected to deflect and propagate along a direction at an angle of 30 • to the original direction of crack propagation. This predicted angle is close to the experimental value of 25 • for PMMA [23], which has been shown to have similar dynamic crack oscillation behavior to polyacrylamide gels [5].…”
Section: ) Crack Branching At High Crack Speedsupporting
confidence: 85%
“…In [4], Ru derived a complete solution for an interface crack in a harmonic elastic bimaterial. For dynamic cracks in hyperelastic materials, more recently, Bouchbinder et al [5] and Livne et al [6] showed that some predictions given by linear elastic fracture mechanics are in direct contradiction with experiment observation of a moving crack tip. These authors stressed the importance of finite-strain analysis for a physically realistic description of moving cracks in hyperelastic materials.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, as long as a single crack retains its path stability (42)) as a free parameter (solid lines). Adapted from [184].…”
Section: Cracking a Dynamic Crack Instabilitymentioning
confidence: 99%
“…Recently, these issues have been addressed in the framework of the "Weakly nonlinear theory of fracture" [1,[34][35][36][37]. This theory is based on a general expansion of the strain energy functional U in the form…”
Section: Weakly Nonlinear Theory Of Fracture Near-tip Fields and Intr...mentioning
confidence: 99%